DAMPAK PEMBANGUNAN KAWASAN MEGAMAS MANADO TERHADAP KONDISI MASYARAKAT DI KELURAHAN WENANG SELATAN - Gratsia Valery Tumurang; Agnes E. Loho; Leonardus R. Rengkung (Sam Ratulangi University, 2018)
This study aims to determine the impact due to the development of Megamas Regions on the condition of the community in South Wenang Urban Village. This study requires secondary data and primary data taken from kelurahan and community as respondents. Data collection is done by survey based on questionnaire compiled. The number of samples taken 30 respondents. The data analysis used in this research is descriptive analysis by explaining all aspects related to the impact caused by Megamas area development. The results of the research show that the development of the Megamas Area has a good social and economic impact, in the form of positive and negative impacts. Some positive impacts are increased income and welfare, employment, business opportunities and recreation, while negative impacts are decreasing income, consumptive, commotion/discomfort, job loss and reduced hygiene.*lrr*.